DETERMINANTS OF TURISM POLICY IN POLAND IN THE ASPECT OF GLOBALLISATION, ECONOMIC, CRISIS AND POLISH PRESIDENCY IN THE EUROPEAN UNION - Panasiuk, Aleksander (Acta Scientiarum Polonorum. Oeconomia, 2010)
Position of the state on the tourism market is determined by many factors. The aim of the paper is presentation of bases of tourism policy and its determiners as well as reference to the current issues of policy making by the state like: globalization, economic crisis and Polish presidency in the European Union. Those factors should be treated as a priority in the current tasks of the state. It should be assumed that inclusion of issues of globalization and economic crisis in the tourism policy results in the possibilities of infl uencing tourism policy in the long term. Polish presidency in the European Union in the second half of the year 2011, although strictly described by the time frames, should enable realization of not only current goals but also long time goals such as e.g. strengthening Polish position as a place of destination on the European tourism market, infl uence on European Union’s regulations in the field of tourism etc.